Microscopic intraneural perineurial cell proliferations in patients with neurofibromatosis type 1 - Agaimy, Abbas (Annals of Diagnostic Pathology, 2014)
Benign peripheral nerve sheath tumors (PNSTs) showing more than one line of differentiation (hybrid PNSTs) have been increasingly recognized, mainly due to awareness of their existence and as a consequence of increased use of immunohistochemisty during the last decade. Two recent studies suggested overrepresentation of hybrid tumors among benign PNSTs in patients with neurofibromatosis type 1 (NF-1). This study was performed to assess the presence of perineurial cells in microscopic (early) neurofibromatous lesions and normal-looking peripheral nerves in specimens from 5 patients with NF-1 using markers of perineurial cell differentiation (epithelial membrane antigen, claudin-1, and glucose transporter 1). In 2 patients, multiple normal looking nerve fibers as well as hypertrophied nerves and microscopic tumor nodules showed variable intraneural perineurial cell proliferations that frequently occupied the whole nerve fascicle resulting in multiple microscopic reticular perineurioma-like nodules (microscopic hybrid neurofibromatosis/perineuriomatosis). None of the cases showed the onion skin pattern of intraneural perineurioma. However, other nerve fibers within the same specimens showed normal compact rim of perineurium without any detectable intraneural perineurial cells. Both patients had concurrent multiple larger PNSTs (plexiform neurofibromas, hybrid neurofibroma/perineurioma and lesions with features intermediate between the 2 types). One specimen harboring high-grade malignant PNST and 2 specimens with large solitary neurofibromas displayed no intraneural perineurial cells. These observations suggest that intraneural perineurial proliferations are part of the early lesions in the setting of constitutional NF-1 inactivation and support the concept of pure and hybrid perineuriomatous lesions as novel member of the spectrum of PNSTs in NF-1.
EVALuna2:6576